Positifikasi Asketisme dalam Islam dengan Pendekatan Paradigma Klasik dan Modern - Nurkhalis Nurkhalis (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Asceticism in Islam is perceived as an ascetic (zuhd), the alienation of self and soul to be more focus in practicing pure worship (ibadah mahdhah). It is not logical if asceticism in Islam is synonymous with faqir (the poor) or ju'i (hungry) or distancing oneself from the crowd and togetherness. The concentration of asceticism attempts to create goodness and virtue, physical strength, emotion and mood. Thus, the introduction of Islamic asceticism to zuhd is included in the historical iron cage, whereas contemporary Islamic asceticism should be included in iron cage of modernity. Islamic asceticism is motivated by ethos and ethics that are socio-centric, not egocentric who only wants perfection and self righteousness. The pattern of Islamic asceticism is not stagnant zuhd but moderate zuhd as the attitude that promotes excellence and achieves all lawful things by performing various contributions to social salvation. Therefore, moderate zuhd equals to productive and participatory zuhd.